2019
DOI: 10.1111/jfbc.12996
|View full text |Cite
|
Sign up to set email alerts
|

Antityrosinase mechanism of ellagic acid in vitro and its effect on mouse melanoma cells

Abstract: The activities of ellagic acid in inhibiting mushroom tyrosinase and cell proliferation were evaluated in this research. The results of enzyme kinetics indicated that ellagic acid could effectively inhibit tyrosinase activity. The value of the semi‐inhibitory rate (IC50) was 0.2 ± 0.05 mM. Ellagic acid inhibited tyrosinase activity in a reversible manner and was a mixed tyrosinase inhibitor. Furthermore, ellagic acid had a good inhibitory effect on the proliferation of mouse melanoma B16 cells and could induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…The number of melanocytes was significantly decreased in Group C,(Table -2,column-4 & 5), compare to control group A. This was due to inhibition of melanocyte proliferation by ellagicacidrichpomegranate 28 proving that ellagic acid possesses strong inhibitory effects on proliferation of melanocytes.…”
Section: Groupmentioning
confidence: 85%
See 1 more Smart Citation
“…The number of melanocytes was significantly decreased in Group C,(Table -2,column-4 & 5), compare to control group A. This was due to inhibition of melanocyte proliferation by ellagicacidrichpomegranate 28 proving that ellagic acid possesses strong inhibitory effects on proliferation of melanocytes.…”
Section: Groupmentioning
confidence: 85%
“…It was observed that no significant effects were exhibited on the mean thickness of epidermis, melanin pigmentation deposition and extension as well as number of melanocytes when compared to control group A. 26,27,28…”
Section: Groupmentioning
confidence: 90%
“…EA is a type of polyphenol compound, widely used in Chinese herbal medicines, such as sanguisorba officinalis and pomegranate peel ( 27 , 28 ). Numerous studies have demonstrated that EA possesses multiple biological activities in vitro ( 14 , 29 , 30 ). The present study explored whether EA could prevent the HG-induced injury of MCs and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated in a constant temperature incubator with 5% CO 2 at 37˚C. When the cells grew to 80% confluency, they were treated as follows: i) Normal control group (NC), MCs were cultured in DMEM with 5.5 mM glucose; ii) HG group, MCs were cultured in DMEM with 30 To detect the cytotoxic effect of EA on MCs, different concentrations of EA (0, 1, 5, 10, 20, 40 or 80 µM ) or 20 µM LY294002 were incubated with MCs under low glucose conditions at 37˚C for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly when we look at our results, the Nrf‐2 protein expression level increased in the EA + CCl 4 group by EA administration in comparison to the CCl 4 group. Huang, Chai et al (2019) stated that treatment with EGCG in rats exposed to formaldehyde, the EGCG antagonized formaldehyde‐induced neurotoxicity in a dose‐dependent manner by activating the Nrf‐2 signaling pathway. Firdaus et al (2018) investigated the preventive effect of EA against neurotoxicity in arsenic treated rats.…”
Section: Discussionmentioning
confidence: 99%